Role of P-glycoprotein in the pharmacotherapy of pregnant women - N. M. Popova; A. V. Shchulkin; I. V. Chernykh; A. S. Esenina; M. M. Gradinar; E. N. Yakusheva (Акушерство, гинекология и репродукция)
This review addresses the function of the protein-transporter glycoprotein-P (Pgp, ABCB1 protein) and the expression of its encoding gene MDR1/mdr1 throughout the gestational period in humans and animals. We discuss the relationship between the transporter function and the hormone fluctuations during pregnancy. We cite studies on the association between the MDR1/mdr1 gene polymorphisms and the hemato-placental barrier permeability for Pgp substrates, as well as fetal malformations. Under a separate section, drugs commonly used in pregnant women are characterized in terms of their roles as substrates, inducers or inhibitors of the Pgp transporter.